Dimerization underlies the aggregation propensity of intrinsically disordered coiled-coil domain-containing 124 - Tuzlakoglu Ozturk, Merve; Guelluelue, Oemer (Wiley, 2022)
Coiled-coil domain-containing 124 (CCDC124) is a recently discovered ribosome-binding protein conserved in eukaryotes. CCDC124 has regulatory functions on the mediation of reversible ribosomal hibernation and translational recovery by direct attachment to large subunit ribosomal protein uL5, 25S rRNA backbone, and tRNA-binding P/A-site major groove. Moreover, it independently mediates cell division and cellular stress response by facilitating cytokinetic abscission and disulfide stress-dependent transcriptional regulation, respectively. However, the structural characterization and intracellular physiological status of CCDC124 remain unknown. In this study, we employed advanced in silico protein modeling and characterization tools to generate a native-like tertiary structure of CCDC124 and examine the disorder, low sequence complexity, and aggregation propensities, as well as high-order dimeric/oligomeric states. Subsequently, dimerization of CCDC124 was investigated with co-immunoprecipitation (CO-IP) analysis, immunostaining, and a recent live-cell protein-protein interaction method, bimolecular fluorescence complementation (BiFC). Results revealed CCDC124 as a highly disordered protein consisting of low complexity regions at the N-terminus and an aggregation sequence (151-IAVLSV-156) located in the middle region. Molecular docking and post-docking binding free energy analyses highlighted a potential involvement of V153 residue on the generation of high-order dimeric/oligomeric structures. Co-IP, immunostaining, and BiFC analyses were used to further confirm the dimeric state of CCDC124 predominantly localized at the cytoplasm. In conclusion, our findings revealed in silico structural characterization and in vivo subcellular physiological state of CCDC124, suggesting low-complexity regions located at the N-terminus of disordered CCDC124 may regulate the formation of aggregates or high-order dimeric/oligomeric states.
Keywords: BiFC; CCDC124; dimerization; intrinsically disordered protein; protein aggregation